“Efecto de la época del corte en el manejo de soca del cultivo de arroz (oryza sativa L.) variedad capirona, bajo el sistema de riego por inundación en el valle Bajo Mayo- San Martín” - Vela Satalaya, Jaro (2003)
January 2003 with the objective of determining the effect of the time of stubble court far rice soca, variety Capirona · under the transplant system, this experiment was carried out in the 1 am founded of Mrs. Carmen García Ramírez located in Morales' district, county and department of San Martin, located geographically at 6° 29' of south latitude; 76° 21 ' longitude west, with an altitude of 350 msnm, you uses the statistical design (DBCR) with 12 treatments carrying out stubble courts to the same day, 3, 6, 9, 12, 15, 18, 21, 24, 27, 30 days and without stubble court like witness; with 3 repetitions. Each experimental unit of 15 m 2 ascending to a total of 45 m2 in which one carries out manua: deshierbo, fertilization and it harvests, in the soca cultivation intermittent waterings and periodic floods were used, you fertilizes to reason of 100-50-80 complementary dose in 2 times to the equivalent 1 O days at 60% of urea and the second to the cotton point to the equivalent 50 days to 40% of the rest of urea. The obtained results indicate that among the studied e treatments highly significant difference existed for the grain yield standing out the stubble cut to the same day, 3 and 6 days after the crop in plant with 4446,67; 4000,00; 3900,00 kg/ha followed by the other treatments with 3380,00; 3260,00; 3020,00; 2833,33; 2733,33; 2706,67; 2633,33; 2360,00 and 2320,00 kg/ha to 14% of humidity approximately.